Study on Law of Overlying Strata Breakage and Migration in Downward Mining of Extremely Close Coal Seams by Physical Similarity Simulation - Xiaobin Li; Wenrui He; Zhuhe Xu (Advances in Civil Engineering)
Extremely close coal seam groups are widely distributed in China, and the main mining method is downward mining. In the downward mining process of extremely close coal seam groups, the violent movement of overlying strata will cause the redistribution of surrounding rock stress. It not only produces stress concentration on the pillar but also causes the roof of the lower coal seam to be broken and difficulty in maintaining the mining roadway. In this study, the physical similitude modeling method and field observations were used to study the breakage and migration law of overlying strata in the downward mining of extremely close coal seams. Results show that in the process of mining upper coal seam, the first weighting step of the main roof is 37.5 m and the periodic weighting step is 12.5 m. The occurrence of strata separation is beneficial to the prediction of roof weighting. When the working face advances to 25 m, the rock stratum approximating a parallelogram of height 5 m does not collapse, and the working face is relatively dangerous. When mining the lower coal seam, the overall pressure of the working face is large, but the periodic weighting of the working face is not obvious. The first collapse step of the immediate roof is 15 m. When mining the upper and lower coal seams, the subsidence of the monitoring point increases significantly at 17.5 and 15 m, respectively. The roof collapse of the lower coal seam occurs 2.5 m ahead of that of the upper coal seam. The hydraulic value of the support, roof fall height, and sloughing depth in the entire working face reach the maximum at the coal pillar, and the extreme points at the coal pillar are relatively concentrated. This research provides some guidance for the safe and efficient mining of extremely close coal seams in the future.